The liberal tradition : - Orton, William Aylott (Yale university press, 1945)
The crying need of modern liberalism is for a clearer perception of principle. A great tradition--the oldest and richest in political history--is all but lost in a fog of careless words and empty phrases. Particularly in America, the term "liberal" is being used to cover policies ranging from nineteenth-century laissez faire to dictatorial collectivism; more, it is being deliberately misapplied by persons whose programs, whatever their merits, are in temper and outlook, as to means as well as ends, radically alien to the liberal tradition. This has become possible because the public and the popular press have almost forgotten the existence of political principle in the sense in which Jefferson and Lincoln, Acton and Gladstone understood it; nor have they found in recent events, domestic or international, much to remind them.